Short Communication: Phylogenetic analysis of mango (Mangifera) in Northern Sumatra based on gene sequences of cpDNA trnL-F intergenic spacer - FITMAWATI FITMAWATI; SANDI PRATIWI HARAHAP; NERY SOFIYANTI (Biodiversitas Journal of Biological Diversity, 2017)
Harahap SP, Fitmawati, Sofiyanti N. 2017. Short Communication: Phylogenetic analysis of mango (Mangifera) in Northern Sumatra based on gene sequences of cpDNA trnL-F intergenic spacer. Biodiversitas 18: 715-719. Northern Sumatra is an area with geographical variation. The environmental factors are affected on character plasticity such as found in Anacardiaceae family especially Mangifera genus. The character plasticity of Mangifera members raises a problem in determining clear boundaries between species based on morphological character. Therefore, a molecular approach is necessary to provide a specific character among Mangifera species. This study aimed to reconstruct the phylogeny among Mangifera members in Northern Sumatra based on the sequences of trnLF intergenic spacer. All of the sequences were aligned by using Clustal W and Cladogram was reconstructed by using PAUP by Maximum Parsimony (MP) and Neighbour-Joining (NJ) methods. The MP cladogram produced two in groups i.e., clade I consist of M. odorata1, M. odorata2, M. laurina1, M. laurina2, M. indica, M. zeylanica, M. quadrifida and Mangifera sp. and clade II consisted of M. foetida1 and M. foetida2. Based on the NJ method, it was obtained M. laurina2 which had the highest genetic distance among other members of Mangifera. The trnL-F intergenic spacer with a low sequences variation indicated that this region was highly conserved and had a low evolution rate in Mangifera.